ÚZLIKSIZ KÁSIPLIK RAWAJLANDÍRÍW SISTEMASÍNDA KURS TÍŃLAWShÍLARÍNÍŃ KÁSIPLIK HÁM TESTOLOGIYALÍQ KOMPETENTLIGIN JETILISTIRIW USÍLLARÍ - Turmanov, Q.A. (SCIENCE and SOCIETY, 2025)
This article presents recommendations for developing students' professional and testological competence in the process of continuous professional development. Information is provided on the current state of the teacher's professional and testological competence in the system of continuous professional development and the methods, means, and technologies for its development.